Testicular cancer: The Most Common Malignancy in Young Men – A Review of Current Knowledge on Diagnosis and Treatment - Krycia, Kamila; Mazur , Karolina; Różycka , Karolina; Mulawa, Magdalena; Gałuszka, Aleksandra; Piaszczyńska , Emilia; Matacz , Dominika; Drabik, Sandra; Gałuszka , Maja; Adamczyk , Adrianna (Journal of Education, Health and Sport, 2026)
Background. Testicular cancer is a rare malignancy that primarily affects young men and requires early diagnosis. The diagnosis is based on clinical tests, imaging tests and measurement of tumor markers. Treatment consists mainly of surgery, and further therapeutic management is adapted to the tumor type and stage. Aim. The aim of this study was to review the literature on testicular cancer, including risk factors, prevention, diagnosis, and treatment. Method and Materials. The literature review was conducted based on publications retrieved from the PubMed, Google Scholar, and Web of Science databases, using the keywords: testicular cancer, epidemiology, diagnostics, cancer markers, and treatment. Results. Regular monitoring of risk factors, testicular self-examination and attention to symptoms increase the likelihood of early detection of testicular cancer by patients. Prompt initiation of appropriate therapy allows effective disease control and improves survival outcomes Conclusion. Testicular cancer requires special diagnostic vigilance, and early therapeutic intervention is crucial for effective treatment.